Physiological Activity of Spinal Cord in Children: An 18F-FDG PET-CT Study. Issue 11 (1st June 2015) - Taralli, Silvia; Leccisotti, Lucia; Mattoli, Maria Vittoria; Castaldi, Paola; de Waure, Chiara; Mancuso, Agostino; Rufini, Vittoria
Abstract : Study Design: Retrospective study. Objective: To evaluate, in a pediatric population, 18 F-Fluoro-deoxy-glucose ( 18 F-FDG) metabolic activity of normal spinal cord and to assess the correlation with demographic, clinical, and environmental variables. Summary of Background Data: 18 F-FDG uptake of normal spinal cord is variable in children. The knowledge of physiological metabolism of spinal cord is essential to distinguish normal from pathological findings by positron emission tomography–computed tomography (PET-CT). Methods: We retrospectively evaluated 18 F-FDG positron emission tomography–computed tomography scans from a total of 167 pediatric patients (97 males; 3.9–18.9 yr) divided into 4 age groups (0–4.9 yr, 5–9.9 yr, 10–14.9 yr, and 15–18.9 yr), excluding those submitted to previous or recent therapeutic procedures influencing spinal cord metabolism or with central nervous system diseases. Spinal cord was divided into 3 levels (C1–C7; D1–D6; and D7–L1), and maximum standardized uptake value (SUVmax) of each cord level was measured. Correlations between SUVmax and spinal cord level, age, body weight, sex, type of disease, and season were statistically assessed. Results: Median SUVmax was similar and significantly ( P < 0.01) higher at C1–C7 and D7–L1 levels than at D1–D6 level and it significantly ( P < 0.01) increased with age in all spinal cord levels. A positive and significant association between SUVmax and body weight, female sex, and Hodgkin lymphoma was found. No significant association with season was observed. By multivariate analysis, only weight and female sex remained significant. Conclusion: Knowledge of physiological 18 F-FDG spinal cord activity in children is essential for a correct interpretation of positron emission tomography–computed tomography, especially in oncologic pediatric patients to avoid potential pitfalls. Level of Evidence: N/A Abstract : We retrospectively evaluated 18 F-Fluoro-deoxy-glucose ( 18 F-FDG) uptake of normal spinal cord in 167 pediatric patients. The correlation with demographic, clinical, and environmental variables was performed. 18 F-FDG activity was higher at C1–C7 and D7–L1 levels in females and increased with increasing body weight. No significant association with age, disease, or environmental factors was found.